Suitability Tests for Bacterial Identification and Antibiotic Sensitivity Tests using Microscan Walkaway on Vitek 2 - Ria Pingkan Ganda; Aryati; Sidarti Soehita (Institute of Medico-legal Publications Pvt Ltd, 2021)
Culture or bacterial culture is the gold standard for diagnostic examination to detect the presence ofmicroorganisms in the patient’s body. The development of culture technology and culture-based automaticdevices for diagnostic examination are widely researched. At present, there are several types of automaticblood culture instruments in Indonesia, namely Vitek 2 and Microscan Walkaway. This research aims toanalyze the suitability of bacterial identification and test antibiotic sensitivity of Microscan Walkaway devicefrom Beckman Coulter and Vitek 2 device from Biomerieux as a gold standard. The research conductedwas an observational cross-sectional study. Sampling was done consecutively. The study sample consistedof 202 samples obtained from the results of positive isolates, during January-July 2019 at Dr. Soetomohospital. Positive isolates were examined for bacterial identification and antibiotic sensitivity using Vitek2 and Microscan Walkaway. The results were statistically analyzed using SPSS. Examination of bacterialidentification using the Microscan device showed 34.2% of Gram-positive bacteria and 65.8% of Gramnegative bacteria, whereas with Vitek 2, results showed 34.7% of Gram-positive bacteria and 65.3% ofGram-negative bacteria. Both of these instruments showed identification accuracy of 98.56% for Grampositive bacteria and 100% for Gram negative bacteria with Kappa value: 0.814 and p <0.0001. The resultsof the accuracy test for antibiotic sensitivity of multidrug resistance bacteria showed compatibility with pvalue <0,0001. There is very good agreement between Vitek 2 and Microscan Walkaway in the identificationof bacteria and antibiotic sensitivity.